Trade sanctions and informal employment - Ali Moghaddasi Kelishomi; Roberto Nisticò (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper examines how trade sanctions affect the allocation of workers across formal and informal employment. We analyse the case of the unexpected and unprecedented trade sanctions imposed on Iran in 2012. We use a difference-in-differences approach and compare the probability of working in the informal sector before and after 2012 for individuals employed in industries with pre-existing different levels of exposure to international trade. Combining employment data from the Iranian Labour Force Survey and trade data from Iran's Customs Administration database for the years 2008-14, we find that workers employed in industries initially facing higher exposure to trade are significantly more likely to experience informal employment in the years after 2012 than workers employed in industries with lower trade exposure. This result suggests that, in the short run, the informal sector may absorb a significant fraction of workers displaced by the trade shock caused by the sanctions. We estimate that the increase in informal employment is highest for poorly educated workers, highlighting the unequal labour market consequences of trade sanctions. We exclude that industries differentially exposed to international trade were already following a different trend in the share of informal employment in the years prior to 2012, thus providing empirical support for the validity of our identification strategy. Moreover, we show that our main result holds when accounting for potential sorting issues by an instrumental variable approach. Our findings shed light on a potentially important dimension of labour reallocation whereby trade sanctions can affect the economy of the target country. They also provide important implications for policies designed to address informal employment and to assist trade-displaced workers.
Keywords: E26; F16; F51; O17; 330; exposure to trade; informal employment; labour reallocation; trade sanctions